2011
DOI: 10.2139/ssrn.1849872
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Determinants of Bad Loans: Evidence from Italian Banks

Abstract: In this paper we use a single-equation time series approach to examine the macroeconomic determinants of banks' loan quality in Italy in the past twenty years, as measured by the ratio of new bad loans to the outstanding amount of loans in the previous period. We analyse the quality of loans to households and firms separately on the grounds that macroeconomic variables may affect these two classes of borrowers differently. According to our estimated models: i) the quality of lending to households and firms can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
111
3
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 32 publications
20
111
3
13
Order By: Relevance
“…Singjergji (2013) investigates the main macroeconomic variables in the Albanian banking find that there is a positive and significant relationship between interest rate and credit risk. This confirms previous studies Farhan (2012); Ahmad & Bashir (2013);and Bofondi (2011) indicate that interest rate affects the amount of bad debt in the case of floating interest rate. Therefore, the increase in the debt caused by the increase in payment of interest rates and result in the rise of non-performing loan.…”
Section: Bank Indonesia Certificate Rate/ Bank Indonesia Certificate supporting
confidence: 92%
“…Singjergji (2013) investigates the main macroeconomic variables in the Albanian banking find that there is a positive and significant relationship between interest rate and credit risk. This confirms previous studies Farhan (2012); Ahmad & Bashir (2013);and Bofondi (2011) indicate that interest rate affects the amount of bad debt in the case of floating interest rate. Therefore, the increase in the debt caused by the increase in payment of interest rates and result in the rise of non-performing loan.…”
Section: Bank Indonesia Certificate Rate/ Bank Indonesia Certificate supporting
confidence: 92%
“…This may result in a decrease in revenues of firms and therefore a decrease in their ability to meet their debt obligations. Accordingly, in periods of high economic growth and low unemployment rates borrowers are more able to support debt, consequently resulting in the decline of NPLs (Bofondi and Ropele, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Das and Ghosh (2007) confirmed that GDP growth has contemporaneous impact on loan default in Indian stateowned banks. In Italy, Bofondi and Ropele (2011) clarified that the annual growth rates of GDP has a negative impact on the quality of household loans, whereas unemployment has a negative effect. Utilizing a data set of 26 advanced countries, Nkusu (2011) clarified that deterioration in the macroeconomic environment as proxied by slower growth, higher unemployment is associated with rising NPLs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Quagliariello (2007) concludes that Italian banks'riskiness and pro…tability are a¤ected by the evolution of the business cycle. Using Italian credit registry data, Bofondi and Ropele (2011) …nd that the quality of lending to households and …rms can be explained by a small number of macroeconomic variables mainly related to the general state of the economy, the cost of borrowing, and the burden of debt. Finally, Notarpietro and Rodano (2016) argue that the slowdown in GDP growth following the global …nancial crisis and the European sovereign debt crisis is a major contributor to the rise in bad debts in Italy.…”
Section: Introductionmentioning
confidence: 99%